Role of Dopants in Long-Range Charge Carrier Transport for p-Type and n-Type Graphene Transparent Conducting Thin Films - Bult, Justin B.; Crisp, Ryan; Perkins, Craig L.; Blackburn, Jeffrey L. (Acs Nano, 2013)
Monolayer to few-layer graphene thin films have several attractive properties such as high transparency, exceptional electronic transport, mechanical durability, and environmental stability, which are required in transparent conducting electrodes (TCs). The successful incorporation of graphene TCs into demanding applications such as thin film photovoltaics requires a detailed understanding of the factors controlling long-range charge transport. In this study, we use spectroscopic and electrical transport measurements to provide a self-consistent understanding of the macroscopic (centimeter, many-grain scale) transport properties of chemically doped p-type and n-type graphene TCs. We demonstrate the first large-area n-type graphene TCs through the use of hydrazine or polyethyleneimine as dopants. The n-type graphene TCs utilizing PEI, either as the sole dopant or as an overcoat, have good stability in air compared to TCs only doped with hydrazine. We demonstrate a shift in Fermi energy of well over 1 V between the n- and p-type graphene TCs and a sheet resistance of similar to 50 Omega/sq at 89% visible transmittance. The carrier density is increased by 2 orders of magnitude in heavily doped graphene TCs, while the mobility is reduced by a factor of similar to 7 due to charged impurity scattering. Temperature-dependent measurements demonstrate that the molecular dopants also help to suppress processes associated with carrier localization that may limit the potential of intrinsic graphene TCs. These results suggest that properly doped graphene TCs may be well-suited as anodes or cathodes for a variety of opto-electronic applications.
Keywords: graphene; transparent conductor; charged impurity; scattering; photovoltalcs; conductivity; mobility; transport; temperature-dependent